1983
DOI: 10.1002/1097-0142(19830315)51:6<1171::aid-cncr2820510633>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of endocrine neoplasia with multiple polyposis of the colon

Abstract: Endocrine neoplasms have occasionally been noted in patients with Gardner's syndrome and other polyposis coli (PC) syndromes; 15 such cases were found in a survey of the English literature. This article reports four additional patients with PC in whom occult endrocrine neoplasms were found at autopsy. Four sets of 100 consecutive autopsy reports, each bracketing but excluding one of the above cases, were reviewed. The incidence of endrocrine neoplasia in patients with non‐PC‐colorectal cancer (2/18) was simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Parathyroid adenomas have recently been reported in a Gardner's syndrome patient and in a patient with familial colorectal polyposis who also presented with pituitary and islet cell adenomas (Schneider et al 1980). We are also aware of another patient who presented with a history of colorectal polyposis and who was diagnosed at autopsy as having a massive chromophobe adenoma of the pituitary as well as a small papillary carcinoma of the thyroid.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Parathyroid adenomas have recently been reported in a Gardner's syndrome patient and in a patient with familial colorectal polyposis who also presented with pituitary and islet cell adenomas (Schneider et al 1980). We are also aware of another patient who presented with a history of colorectal polyposis and who was diagnosed at autopsy as having a massive chromophobe adenoma of the pituitary as well as a small papillary carcinoma of the thyroid.…”
Section: Discussionmentioning
confidence: 85%
“…At autopsy, bilateral adrenal cortical adenomas were discovered. Schneider et al (1980) have reported a 36-year-old male who died of a metastatic carcinoid arising in a cecal polyp with adenocarcinoma. At autopsy, an adrenal cortical adenoma was found.…”
mentioning
confidence: 99%
“…Interestingly, patients with family history of colonic polyposis and colorectal cancer have in few cases been associated to endocrine neoplasias, including parathyroid adenomas (29), as well as lesions of the jaws (30). Jaw tumors are also a feature of the HPT-JT syndrome caused by germline HRPT2 mutations, in which the afflicted members may present with PHPT that is frequently malignant, ossifying jaw tumors as well as various lesions of the kidney and uterus (31).…”
Section: Discussionmentioning
confidence: 99%
“…breast, and other common, cancers is not limited to relatives of young patients in all populations. In some studies, familial clustering has been observed regardless of the age of onset of the proband (Schneider et al, 1983; Weiss et al, 1986).…”
Section: Strong and Consistentmentioning
confidence: 99%